Implementation of hazard analysis critical control point (HACCP) on pan–seared butter fish with herb cream sauce in PT AF - Khasanah, Nabila Nur; Kumalasari, Ika Dyah (Universitas Ahmad Dahlan, 2025)
Hazard Analysis Critical Control Point (HACCP) is a quality assurance, food safety, and risk management system with a preventive approach to ensure food safety for consumers. Food served during in–flight travel is provided by in–flight catering. Airline food has very high standards regarding food quality and safety. The purpose of this study is to analyze the application of HACCP to aviation food products by identifying potential hazards and applying Critical Control Points (CCP). The method used in this study is Critical Control Point (CCP) observations, carried out at the receiving (CCP 1), chiller and freezer (Storage) (CCP 2), cooking (CCP 3), blast chilling (CCP 4), and serving (CCP 5) stages. The company has created a HACCP plan as a guide for all processes that occur within the company. All are organized based on HACCP principles for the entire process. Keywords: CCP, Food Safety, HACCP, Inflight Catering, ISO 22000.